2002
DOI: 10.1088/0954-3899/28/7/375
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the strange-quark chemical potential in the phase diagram of nuclear matter

Abstract: On the basis of lattice calculations, we require the existence of a deconfined quark matter region (0 < as < 1) beyond the hadron gas phase, which goes asymptotically into the ideal quark–gluon plasma domain, in the phase diagram of nuclear matter. We consider empirically the dynamics of this region in terms of the order parameters and mass-scaled partition functions and derive an EoS. Then, the strange-quark chemical potential is expressed in a functional form of the temperature and light-quark chemical poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Under the description of standard thermodynamics, by considering an adequate entropy condition S 0, was found that a negative chemical potential allows a phantom behavior (ω < −1), on the other hand, a positive chemical potential restricts the parameter state to take values greater than −1 [11]. In the context of nuclear physics was found that a transition from a positive chemical potential in the hadronic phase to negative quark-gluon phase, represents a physically viable mechanism to describe properly the quark deconfinement [13].…”
Section: Introductionmentioning
confidence: 99%
“…Under the description of standard thermodynamics, by considering an adequate entropy condition S 0, was found that a negative chemical potential allows a phantom behavior (ω < −1), on the other hand, a positive chemical potential restricts the parameter state to take values greater than −1 [11]. In the context of nuclear physics was found that a transition from a positive chemical potential in the hadronic phase to negative quark-gluon phase, represents a physically viable mechanism to describe properly the quark deconfinement [13].…”
Section: Introductionmentioning
confidence: 99%
“…Deduced values for T, µ q , µ s from several thermal models and fits to experimental data for several interactions. Interaction/Experiment Si+Au(14.6 AGeV)/E802 Reference [28] Reference [26] Mean…”
Section: Experimental Datamentioning
confidence: 99%
“…Note that in [23,25,26] the negative µ S refers to the strangeness chemical potential, which is related to the strange-quark chemical potential by: µ S = µ s + µ q . This fact led to a misinterpretation in [28]. However the sulfur-induced interactions may deserve a more cautious examination, as suggested by the SSBM analysis.…”
Section: Experimental Datamentioning
confidence: 99%
“…However, I wish to remain at the affirmative side for a moment. First, particularly Zimanyi and collaborators [16] but also Gazdzicki and Gorenstein [30], Bialas [31] and Panagiotou and collaborators [32] have been daring enough to explore certain more explicit, schematical models of the hadronization transformation. All this models are based on the assumption that a partonic state is reached in the primordial fireball, at top SPS energy.…”
Section: Evidence For the Qcd Phase Transformation?mentioning
confidence: 99%